Food insecurity and mental illness: disproportionate impacts in the context of perceived stress and social isolation. (March 2016) - Martin, M.S.; Maddocks, E.; Chen, Y.; Gilman, S.E.; Colman, I.
Abstract: Objectives: Food insecurity is associated with elevated risk of mental illness. This risk may be further compounded by stressful life events and by social isolation. This study investigated whether the risk of mental illness is higher among individuals experiencing food insecurity along with greater stress and social isolation. Study design: Cross-sectional self-report survey data from the 2009-10 Canadian Community Health Survey ( N = 100, 401). Methods: We estimated prevalence differences of the risk of self-reported mental illness associated with food insecurity alone and in combination with stressful life events and social isolation. Sensitivity analyses were conducted on a sub-sample who completed a structured diagnostic interview. Results: Overall, the prevalence of mental illness was 18.4% [95% CI 16.7–20.1] higher for women and 13.5% higher [95% CI 11.9, 15.2] for men in severely food insecure households compared to those reporting food security. The increased risk of mental illness associated with food insecurity was more pronounced among females and those reporting higher stress and social isolation. Conclusions: Individuals reporting food insecurity are at increased risk of mental illness. This increased risk is further exacerbated in high stress and socially isolated environments. Policies, clinical and public health interventions must address broader constellations of risks that exist when food insecurity is present. Highlights: We studied the co-occurrence of mental illness and food insecurity in a large population survey. Mental illness is more common among individuals experiencing food insecurity. Mental illness and food insecurity co-occur more often among those reporting more stress, weak community belonging and women. Contextual risks (e.g. stigma and gender roles) should be considered in crafting policy and clinical interventions.